2012
DOI: 10.1104/pp.112.200386
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-Associated Molecular Patterns-Triggered Root Responses Mediate Beneficial Rhizobacterial Recruitment in Arabidopsis      

Abstract: This study demonstrated that foliar infection by Pseudomonas syringae pv tomato DC3000 induced malic acid (MA) transporter (ALUMINUM-ACTIVATED MALATE TRANSPORTER1 [ALMT1]) expression leading to increased MA titers in the rhizosphere of Arabidopsis (Arabidopsis thaliana). MA secretion in the rhizosphere increased beneficial rhizobacteria Bacillus subtilis FB17 (hereafter FB17) titers causing an induced systemic resistance response in plants against P. syringae pv tomato DC3000. Having shown that a live pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
135
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 89 publications
(129 reference statements)
3
135
0
1
Order By: Relevance
“…7). While it remains to be investigated whether our transgenic tobacco plants are also resistant to the attack of bacterial pathogens, the expression of Arabidopsis for Aluminum-activated Malate Transporter1 has been documented to be involved in both Al tolerance and pathogen resistance (Rudrappa et al, 2008;Lakshmanan et al, 2012;Kobayashi et al, 2013). In our previous study, a pathogenesis-related gene was found to be up-regulated by Al stress in rice bean .…”
Section: Discussionmentioning
confidence: 99%
“…7). While it remains to be investigated whether our transgenic tobacco plants are also resistant to the attack of bacterial pathogens, the expression of Arabidopsis for Aluminum-activated Malate Transporter1 has been documented to be involved in both Al tolerance and pathogen resistance (Rudrappa et al, 2008;Lakshmanan et al, 2012;Kobayashi et al, 2013). In our previous study, a pathogenesis-related gene was found to be up-regulated by Al stress in rice bean .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas mechanisms of plant defense involving the aerial parts are well documented, there is little knowledge of root responses to soil-borne pathogens (Attard et al, 2010;Millet et al, 2010;Lakshmanan et al, 2012;Wang et al, 2012). Extrapolation of defense responses from the leaves to the root system should be used carefully, since growing evidence suggests that molecular mechanisms are quite different between roots and aerial organs (Attard et al, 2010;Millet et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the malate release helped recruit the beneficial bacterium Bacillus FB17 around the roots [16,31]. Furthermore, AtALMT1 expression was induced by flg22, a kind of MAMP (microbe-associated molecular pattern) in a manner that was independent of the salicylic acid and jasmonic acid pathways [55]. A recent study with Arabidopsis, which also relies on malate efflux via a ALMT1 channel, proposes that the Al:malate complex is taken up by the root cells and transported to shoot by NIP1;2 to maintain low Al concentrations in the apoplast shoots [56].…”
Section: Almt Members In Brassicaceaementioning
confidence: 91%